Efficacy and microbial responses of biochar-nanoscale zero-valent during in-situ remediation of Cd-contaminated sediment. (10th March 2021) - Liu, Qunqun; Sheng, Yanqing; Wang, Wenjing; Liu, Xiaozhu
Abstract: In situ immobilization of heavy metals in sediments has been considered as a low-cost and eco-friendly remediation method. In this study, biochar (BC) and BC-nanoscale zero-valent iron composite (nZVI/BC) treatments with different doses were conducted to immobilize Cd in sediments in situ . The performance of BC and nZVI/BC in changing Cd mobility and bacterial community in sediment was investigated, and their remediation efficiencies at various pH values were also explored. After 140 d of remediation, the results showed that the application of BC and nZVI/BC reduced the released Cd concentrations in the overlying water and porewater by 31–69% and 26–73%, respectively. Compared to the control, the labile Cd in treated sediments was transformed to a stable fraction, and the TCLP (toxicity characteristic leaching produce) extracted Cd decreased by 7–29%. The reduction in Cd mobility was closely related to the additional dose of BC or nZVI/BC, and the presence of nZVI greatly enhanced the ability of nZVI/BC to stabilize Cd. Notably, nZVI/BC presented a higher restriction for Cd release from sediment than BC at various pH values, and both BC and nZVI/BC showed the highest remediation effects under alkaline condition. Bacterial community analysis indicated that the richness and diversity of bacterial communities with the low-dose treatments were enhanced, while inhibition was observed at high dose treatments due to changes in the pH and toxicity of BC and nZVI/BC. This study supplies new insights into the potential effects of BC and nZVI/BC application on Cd in situ immobilization in contaminated sediments. Graphical abstract: Image 1 Highlights: Efficacy of BC and nZVI/BC for Cd immobilization at various pH was explored. The nZVI/BC showed higher inhibition for Cd release than BC at various pH values. Both BC and nZVI presented high remediation effect in alkaline condition. Excessive application of BC or nZVI/BC damaged sediment bacterial community.